Proximate Composition and Fruit Weight of Fresh Date Fruits (Phoenix dactylifera L.) Varieties in Wet Season of Nigeria - Yahaya, S.A.; Omokhudu, C.A.; Koloce, I.M.; Hamza, A.M.; Abdullahi, M.A. (Pakistan Journal of Nutrition, 2015)
The aim of this experiment was to examine the proximate composition and fruit weight of some selected fresh date fruits in wet season of Nigeria in June 2014 during the harvest period. The fresh date fruits varieties were selected from gene pool 4 in the experimental field of Nigerian Institute for Oil palm Research (NIFOR) date palm substation, Dutse, Jigawa State. Results showed that variety-01 had the highest moisture content of (73.60±0.20), while Fat content were recorded highest for Variety-05 (2.96±0.03). However the Ash content was observed in Variety-01 (0.95±0.03), Variety-04 (1.22±0.02) and Variety-05 (0.78±0.01), respectively. A high amount of crude Fibre was recorded in variety-05 with (0.64±0.01) while protein content was least in variety-02 and variety-03 with the means (2.73±0.02) and (2.56±0.01). Carbohydrate content was highest in variety-01 (54.15±0.99) and variety-03 (32.65±0.05), respectively. The results generally indicated that date (Phoenix dactylifera) fruit were good sources of nutrition and can be used in food formulation and future date palm breeding programmes.